1995
DOI: 10.1093/hsw/20.4.294
|View full text |Cite
|
Sign up to set email alerts
|

Does Apologizing Help? The Role of Self-Blame and Making Amends in Recovery from Bereavement

Abstract: This article presents the results of an investigation into the relationship between attributions of self-blame for the death of a loved one and subsequent psychological recovery from this loss. Two hundred and forty-four people who had suffered the death of a loved one identified the emotional, cognitive, and behavioral responses they used at the time of their loss. Data indicated that use of self-blame was associated with poorer long-term adjustment. However, it was also found that self-blame often led people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Couple-focused therapy and group interventions may be particularly effective for helping bereaved parents to develop shame resilience (Brown, 2006). Guilt may be alleviated by apologizing, making amends, forgiving oneself or being forgiven, and contemplating thinking patterns that contribute to guilt (Kubany & Watson, 2003;Weinberg, 1995). Parental involvement in end-of-life caregiving, when possible, should be encouraged.…”
Section: Authors' Conclusion Implications For Practicementioning
confidence: 99%
“…Couple-focused therapy and group interventions may be particularly effective for helping bereaved parents to develop shame resilience (Brown, 2006). Guilt may be alleviated by apologizing, making amends, forgiving oneself or being forgiven, and contemplating thinking patterns that contribute to guilt (Kubany & Watson, 2003;Weinberg, 1995). Parental involvement in end-of-life caregiving, when possible, should be encouraged.…”
Section: Authors' Conclusion Implications For Practicementioning
confidence: 99%
“…One study reported higher guilt in natural compared with unnatural death (Bailley, Kral, & Dunham, 1999), other studies reported the opposite pattern (Gamino, Sewell, & Easterling, 2000;Hazzard, Weston, & Gutterres, 1992;Weinberg, 1995), and one study found no group difference (Harwood, Hawton, Hope, & Jacoby, 2002). Suicide survivors have been described as more vulnerable to guilt than following other types of bereavement (Jordan, 2001).…”
Section: Risk Factorsmentioning
confidence: 99%
“…One study found a positive correlation between guilt and psychiatric as well as traumatic reactions (Mizota et al, 2006), and another two documented an association between guilt and impaired physical health (Hazzard et al, 1992;Kowalski & Bondmass, 2008). The association between guilt and greater maladjustment is also reflected in positive correlations between guilt and normal or complicated grief symptoms (Akiyama et al, 2010;Boelen & Lensvelt-Mulders, 2005;Boelen, van den Bout, & van den Hout, 2003;Field et al, 2000;Gamino et al, 2000;Mizota et al, 2006;Weinberg, 1994Weinberg, , 1995. Lastly, an inverse relationship between guilt and positive outcome after bereavement further confirms the association between guilt and maladaptive health outcomes (Gamino et al, 2000).…”
Section: Guilt and Health Outcomesmentioning
confidence: 99%
“…Again, the client needs to understand what the goals of bereavement work are such as disempowerment of the abuser, forgiveness, decreasing self-blame, understanding the abuse, and ultimately assisting in the bereavement process (Weinberg, 1995). After assessing readiness, clinicians may want to encourage the client to join a bereavement group or an abuse survivors group.…”
Section: Further Issues In Bereavement Workmentioning
confidence: 99%